Efektivitas Model Project Based Learning dalam Pembelajaran Pendidikan Pancasila Untuk Meningkatkan Civic Disposition Peserta Didik (Penelitian Quasi Eksperimen di Kelas XI Madrasah Aliyah Darurrahman Kecamatan Pacet Kabupaten Bandung) - Andini Azkiya Fadila; Dadang Mulyana; Cahyono Cahyono (GLOBAL SCIENTS PUBLISHER, 2026)
This study was motivated by the low level of students’ civic disposition in Pancasila Education, as reflected in their lack of responsibility, collaboration, and active participation during the learning process. This study aimed to analyze the effect of the Project Based Learning (PjBL) model on improving students’ civic disposition, identify the differences in civic disposition between students taught using the Project Based Learning (PjBL) model and those receiving conventional instruction, and examine the effectiveness of the Project Based Learning (PjBL) model in enhancing the civic disposition of eleventh-grade students at MA Darurrahman. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of Class XI-3 as the experimental group and Class XI-2 as the control group, selected through purposive sampling. Data were collected using questionnaires, observation sheets, and pretest–posttest assessments. Data analysis included descriptive statistics, the Wilcoxon Signed-Rank Test, the Mann–Whitney U Test, Effect Size, and N-Gain. The findings indicated that the implementation of the Project Based Learning (PjBL) model had a significant effect on improving students’ civic disposition, as evidenced by the Wilcoxon Signed-Rank Test significance value of 0.000 (<0.05) and an Effect Size of 0.863, which was classified as a large effect. Furthermore, the Mann–Whitney U Test yielded an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), indicating a significant difference in civic disposition between the experimental and control groups. The N-Gain score of 0.5928, categorized as moderate, further supported the effectiveness of the Project Based Learning (PjBL) model. Therefore, the Project Based Learning (PjBL) model proved to be effective in improving students’ civic disposition in Pancasila Education.